2020
DOI: 10.1093/femsec/fiaa078
|View full text |Cite
|
Sign up to set email alerts
|

The marine intertidal zone shapes oyster and clam digestive bacterial microbiota

Abstract: Digestive microbiota provide a wide range of beneficial effects on host physiology and are therefore likely to play a key role in marine intertidal bivalve ability to acclimatize to the intertidal zone. This study investigated the effect of intertidal levels on the digestive bacterial microbiota of oysters (Crassostrea gigas) and clams (Ruditapes philippinarum), two bivalves with different ecological niches. Based on 16S rRNA region sequencing, digestive glands, seawater and sediments harbored specific bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 73 publications
5
37
0
Order By: Relevance
“…Microbial communities showed significant variation across sample types: seawater, marine sediment, oyster shell biofilm and oyster gut. The gut of the oyster hosted the lowest diversity of bacteria, which has been demonstrated previously in comparison to the surrounding water and sediment (Arfken et al 2017;Offret et al 2020). Beta diversity analysis suggests that the gut microbiome was significantly different from the microbiome found on the shell or in surrounding seawater.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Microbial communities showed significant variation across sample types: seawater, marine sediment, oyster shell biofilm and oyster gut. The gut of the oyster hosted the lowest diversity of bacteria, which has been demonstrated previously in comparison to the surrounding water and sediment (Arfken et al 2017;Offret et al 2020). Beta diversity analysis suggests that the gut microbiome was significantly different from the microbiome found on the shell or in surrounding seawater.…”
Section: Resultsmentioning
confidence: 57%
“…In this study, Mycoplasma and an unidentified bacterial group made up a high percentage of the total community and were found in over 75% of oyster gut samples. Mycoplasma is a genus of the Mollicutes class and have been found in high proportions in various oyster species across a broad geographic range (G. M. King et al 2012;Offret et al 2020;Arfken et al 2017). One study demonstrated that Mycoplasma are likely relying on the oyster to provide certain compounds (Pimentel et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in the digestive glands of the oyster (Crassostrea Gigas) and clam (Ruditapes philippinarum) from France, the Mycoplasmaceae, Desulfobacteraceae, and Rhodobacteraceae families were reported as the most abundant taxa by Offret et al [55]. Interestingly, byssus gland and hemolymph tissues of the oyster Pinctada margaritifera from lagoons of Takapoto atoll (French Polynesia), Rhodobacteraceae, and Flavo-bacteriaceae families were found as abundant taxa, but members of Myco-plasmataceae were not found [56]. Although significant differences (p ≤ 0.05) were not observed in all statistical parameters estimated in this study, in general terms, the analysis of alpha diversity showed higher observed OTUs and phylogenetic diversity in tissue samples from the Nehuentue estuary than in those from Hueihue Bay, whereas higher values of diversity (Shannon and Inverse Simpson indexes) and Pielou's Evenness Index were found in tissue samples from Hueihue Bay.…”
Section: Discussionmentioning
confidence: 90%
“…Being lter-feeders, bivalves interact with numerous microorganisms coming from the environment. They maintain tissue-speci c microbiota that differ from that of their surrounding environment [9], indicating that both organisms and tissues select the bacteria they host lters [10,11]. Nonetheless, these host-associated microbiota may vary spatially and temporally re ecting seasonal changes and geographic location [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%